2009
DOI: 10.2341/08-026-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phosphoric Acid Etching of Enamel Margins on the Microleakage of a Simplified All-in-One and a Self-etch Adhesive System

Abstract: This study evaluates the effect of phosphoric acid etching of enamel margins on the microleakage of a simplified all-in-one and a self-etching adhesive system in comparison to a conventional total-etch system. SUMMARYSixty buccal Class V cavities with beveled enamel margins were made at the cemento-enamel junction of extracted human premolars and randomly divided into five groups of 12 specimens. Clearfil SE bond was applied to Group 1; Group 2 had 35% phosphoric acid etching of the enamel margins plus Clearfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…[31] Khosravi et al . [32] also concluded that simplified all-in-one adhesive systems need pre-etching of the enamel margins with phosphoric acid for an effective seal. Therefore, the null hypothesis that prior acid etching did not affect the microleakage was rejected.…”
Section: Discussionmentioning
confidence: 99%
“…[31] Khosravi et al . [32] also concluded that simplified all-in-one adhesive systems need pre-etching of the enamel margins with phosphoric acid for an effective seal. Therefore, the null hypothesis that prior acid etching did not affect the microleakage was rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, enamel pre-etching with phosphoric acid is recommended to improve adhesion. 20 Limited evidence is available regarding microleakage with the use of the HEMA-based adhesives One Coat 7.0 and Optibond All-In-One. HEMA improves the miscibility of hydrophobic and hydrophilic adhesive components.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that bonding of restorative materials to enamel with total-etching adhesive systems is adequate to resist contraction stress [29][30][31] . Thus, several studies have demonstrated more microleakage at the enamel margin when self-etching adhesive systems were used 32,33) . Low amounts of microleakage occurring along the enamel margins were shown.…”
Section: Discussionmentioning
confidence: 99%